Simulation of Wellbore Stability during Underbalanced Drilling Operation - Reda Abdel Azim (Journal of Applied Mathematics)
The wellbore stability analysis during underbalance drilling operation leads to avoiding risky problems. These problems include (1) rock failure due to stresses changes (concentration) as a result of losing the original support of removed rocks and (2) wellbore collapse due to lack of support of hydrostatic fluid column. Therefore, this paper presents an approach to simulate the wellbore stability by incorporating finite element modelling and thermoporoelastic environment to predict the instability conditions. Analytical solutions for stress distribution for isotropic and anisotropic rocks are presented to validate the presented model. Moreover, distribution of time dependent shear stresses around the wellbore is presented to be compared with rock shear strength to select appropriate weight of mud for safe underbalance drilling.